(untitled) (Linguostylistic Studies, 2022)
This article examines the functions of the Ukrainian language in the church and religious life of the autochthonous Ukrainians in the interwar Poland. The research aim is to substantiate the content of a new concept in historical sociolinguistics. To achieve the goal, the author analyzes the communicative practices of Ukrainians before 1918 and their conscious influence on the development of the native language functions in church and religious life after 1918. The theoretical background of the research is premised on views expressed by historians, religious scholars and sociolinguists. More than 50 texts of various genres served as sources of analysis, including ego-sources, scientific works of event participants, published archival church documents, etc. The elements of discourse analysis, the biographical method and the method of sociolinguistic reconstruction are applied to the units under analysis (more than 200 meta-linguistic textual pieces of evidence). The analyzed database illustrates the conscious influence on the development of the functions of the Ukrainian language in two directions: by supporting it in the decisions of church congresses or societies and in spiritual education. The conclusions of the article testify that the meaning of the concept reflects the Ukrainianization process in the Orthodox Church, initiated by the Ukrainian clergy and intelligentsia, supported by believers, but terminated by the state authorities in 1937. The obtained results of the analysis make it possible to introduce into Ukrainian historical sociolinguistics not only the new concept of “the functions of the Ukrainian language in the church and religious life of the Orthodox believers of the Second Polish Republic (1918–1939)”, but also the term of the same name.